Effect of multi‐epoxy compatibilizers with branched structures on enhancing mechanical and compatibility of PLA/starch composite. (9th February 2023) - Yu, Chongdong; Feng, Jianxiang; Feng, Kailin; Mo, Zhixiang; He, Yulin; Wang, Qingting; Yu, Anyang; Leng, Zhiwen; Shi, Pu; Liu, Yuejun
Abstract: Polylactic acid/starch (PLA/ST) composites are all sustainable origin, have huge cost advantages and degradation tendency to replace petroleum‐based plastics. However, thermodynamic incompatibility between PLA and starch dragged the performance far below expectations. Considering that ethylene glycol diglycidyl ether (EGDE), glycerol triglycidyl ether (GTE), and pentaerythritol glycidyl ether (PGE) have branched multi‐epoxy structure, high epoxy value, and excellent wettability, we firstly explored those materials as compatibilizers in PLA/ST composites. The reactive compatibilization between the epoxy groups on EGDE, GTE, and PGE with the hydroxyl groups on PLA and ST is confirmed by Fourier transform infrared spectroscopy (FT‐IR) analyses. The mechanical properties show that the introduction of only 3 wt% GTE in PLA/ST composites can induce the tensile strength and elongation at break to be increased by 80% and 38%, respectively. The rheological tests indicate that the introduction of only 3 wt% GTE in PLA/ST composites increased the slopes of Han plots from 0.48 to 0.88. Differential scanning calorimetry (DSC) analyses show that the crystallinity increases with the content of compatibilizer, up to 31%. The reduction of the gap between PLA and starch interfaces characterized by Scanning Electron Microscope (SEM) demonstrated that the compatibility of PLA and ST was improved. Furthermore, the effects of EGDE, GTE, and PGE with the same epoxy value but different branch chains on the compatibilization of PLA/ST blends are further discussed. The results show that GTE and PGE with star‐shaped branched structure has a better compatibilization effect on PLA/ST blends than EGDE with linear branched structure.